Adsorption of Carbon Monoxide (CO) on ZSM-5 Membrane in Smoking Area - Azizah, Inas Hasna; Mindhumalid, Tatut; Mukaromah, Ana Hidayati (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
This research aimed to investigate the ability of ZSM-5 in absorbing cigarette smoke to reduce CO level in smoking area. The research method are according to Gao, 2011 and Mukaromah 2014. The results were characterized using x-ray diffraction (XRD), FTR and SEM. The absorbance test was conducted by placing the gauze absorbed into the enclosed space with volume 18.000 cm3containing CO from cigarette smoke. The research was reached the stage of inorganic and organic substances leaching and oxidized in electrochemistry in H2SO4 to 20%. Zeolite zsm-5 membrane has the ability to absorb CO with the decline in CO on the highest levels the surface area of 25 cm2 to the time contact 30 minutes is 0.50 %.